2018
DOI: 10.1038/s41388-017-0114-y
|View full text |Cite
|
Sign up to set email alerts
|

FYN promotes mesenchymal phenotypes of basal type breast cancer cells through STAT5/NOTCH2 signaling node

Abstract: Basal type breast cancer is the most aggressive and has mesenchymal features with a high metastatic ability. However, the signaling node that determines the basal type features in breast cancer remains obscure. Here, we report that FYN among SRC family kinases is required for the maintenance of basal type breast cancer subtype. Importantly, FYN enhanced NOTCH2 activation in basal type breast cancer cells through STAT5-mediated upregulation of Jagged-1 and DLL4 NOTCH ligands, thereby contributed to mesenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 30 publications
1
45
0
1
Order By: Relevance
“…To investigate the interactive effects among genes of survival-related AS events, the top significant survival-associated genes in the OSCC cohort were uploaded to Cytoscape to generate an inter-gene interaction network. Several hub genes like PRKACA, CDC42, and FYN were identified (Figure 3b), which had previously been found to be associated with different cancers (Kastenhuber et al, 2017;Lee et al, 2018;Min et al, 2019).…”
Section: Identification Of Survival-associated As Events In Osccmentioning
confidence: 84%
“…To investigate the interactive effects among genes of survival-related AS events, the top significant survival-associated genes in the OSCC cohort were uploaded to Cytoscape to generate an inter-gene interaction network. Several hub genes like PRKACA, CDC42, and FYN were identified (Figure 3b), which had previously been found to be associated with different cancers (Kastenhuber et al, 2017;Lee et al, 2018;Min et al, 2019).…”
Section: Identification Of Survival-associated As Events In Osccmentioning
confidence: 84%
“…The Notch pathway cooperates in the initiation and progression of breast cancer metastasis. Lee et al [8] found that the protein kinase Fyn plays a significant role in promoting breast cancer tumorigenicity via the Notch2 signaling pathway. Hu et al [9] found that the application of Brucine could inhibit Notch1 pathway and thereby reduce bone metastasis of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Karsan and colleagues showed that Slug is a direct target gene of Notch1 in breast cancer (Leong et al, 2007). In line with these findings, Suh and colleagues demonstrated that Notch2 up-regulates multiple EMT-associated markers including Twist, Snail1, Slug, Vimentin, and Zeb1 in basal type breast cancer cells (Lee et al, 2018). Clinical studies performed in breast cancer patients demonstrate that Notch signaling activation is associated with reduced overall survival and poor prognosis (Reedijk et al, 2005;Dickson et al, 2007), underscoring the importance of this signaling pathway for tumor progression in human breast cancer.…”
Section: Notch Pathwaymentioning
confidence: 80%